Effect of market orientation, entrepreneurial orientation and technology orientation on business performance - Indah Permata Sari; Thamrin Thamrin (Universitas Negeri Padang, 2022)
The purpose of this study was to analyze the effect of entrepreneurial orientation, market orientation and technology orientation on business performance in the Bilih fish business of Danau Singkarak Kenagarian Guguak Malalo. The population in this study were all business owners of Ikan Bilih Danau Singkarak Kenagarian Guguak Malalo. The number of samples in this study was obtained with a total sampling of 45 samples. The analysis technique used is multiple regression. The results of this study indicate that entrepreneurial orientation, market orientation and technology orientation have a significant influence on business performance in the Bilih Fish business of Danau Singkarak Kenagarian Guguak Malalo.